Cu (II) ions removal from water by charcoal obtained from marigold flower waste. (2021) - Agarwal, Anupam; Kumar, Amit; Gupta, Pankaj; Tomar, Richa; Singh, N.B.
Graphical abstract: Abstract: Flower waste management is becoming a very challenging problem due to the huge time requirement for its segregation and biodegradation. Charcoal prepared using flower waste can be considered as an effective adsorbent for wastewater remediation. In this study marigold flower waste was used to prepare charcoal, and characterization was done using SEM and EDS. The marigold flower charcoal (MFC) was used for adsorption study of Cu (II) metal ions from aqueous solution. Modelling of adsorption isotherm showed that adsorption data is best fitted with Temkin isotherm and Dubinin-Radushkevich isotherm. The values of n and E are less than one which supports the physical adsorption of Cu (II) ions onto MFC. In summary the data obtained is very significant to utilize the flower waste for water remediation.